2019
DOI: 10.21608/mjcu.2019.59202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pentoxifylline Administration on Hemoglobin Level of Hemodialysis Patients

Abstract: Background: Anemia is a common complication of endstage renal disease despite sufficient iron stores. That is mainly due to the effect of chronic inflammation. Aim of Study:Our study investigated the effect of using a know drug used in intermittent claudication (named pentoxifylline) as an adjuvant to ESA to improve anemia of hemodialysis patients. Patients and Method:Fifty hemodialysis anemic patients were included. They were assigned to two groups of equal numbers. Oral Pentoxifylline 400mg once daily was ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, our results align with these ndings, El-Haggar and Mostafa observed that PTX signi cantly reduced GGT levels in NASH patients [54]. Consistent with our results, Mohamed et al reported that patients treated with PTX for 6 months at a dose (400 mg/once a day) showed signi cant elevation in albumin level [55]. A preceding study by Taye et al showed that PTX administration to rats led to a marked rise in serum albumin level and decreased serum ALP level [56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results align with these ndings, El-Haggar and Mostafa observed that PTX signi cantly reduced GGT levels in NASH patients [54]. Consistent with our results, Mohamed et al reported that patients treated with PTX for 6 months at a dose (400 mg/once a day) showed signi cant elevation in albumin level [55]. A preceding study by Taye et al showed that PTX administration to rats led to a marked rise in serum albumin level and decreased serum ALP level [56].…”
Section: Discussionmentioning
confidence: 99%